Rapid Screening for Flavone C-Glycosides in the Leaves of Different Species of Bamboo and Simultaneous Quantitation of Four Marker Compounds by HPLC-UV/DAD - Jin Wang; Yong-de Yue; Hao Jiang; Feng Tang (International Journal of Analytical Chemistry)
A strategy for analyzing flavone C-glucosides in the leaves of different species of bamboo was developed. Firstly, the flavone C-glycosides were extracted from the bamboo leaves (51 species in 17 genera) with methanol and chromatographed on silica gel 60 plates in automatic developing chamber (ADC2), and a qualitative survey using simple derivatization steps with the NP reagent was carried out. The flavone C-glycosides were found in 40 of 51 species of bamboo examined. Secondly, an HPLC method with photodiode array and multiple wavelength detector was optimized and validated for the simultaneous determination of flavone C-glycosides, including isoorientin, isovitexin, orientin, and vitexin in the leaves of three species of bamboo and the flavone C-glycosides were confirmed by LC/MS. The optimized HPLC method proved to be linear in the concentration range tested (0.2–100 μg/mL, r2≥0.9997), precise (RSD≤1.56%), and accurate (88–106%). The concentration ranges of isoorientin, isovitexin, orientin, and vitexin in three bamboo leaves samples were 1.00–2.78, 0–0.31, 0–0.07, and 0.20–0.68 mg/g, respectively. The proposed method was validated to be simple and reliable and can be a tool for quality control of bamboo leaf extract or its commercial products.